Recent Advances in Room-Temperature Direct C–H Arylation Methodologies - Yadav, Preeti; Velmurugan, Nivedha; Luscombe, Christine K. (Synthesis, 2022)
In recent decades, direct C–H arylation has become a preferred tool for biaryl coupling over traditional cross-coupling methods owing to its operationally simple protocol, inherent atom and step economy, and reduced metallic waste. Several elegant methods have been developed that offer the facile transformation of usually inert Csp2–H bonds into Csp2–Csp2 bonds in a single synthetic operation. Despite many merits, a major drawback to this chemistry comes from the low reactivity of aryl C–H bonds, which often mandate harsh reaction conditions compromising sustainability. Hence, developing reaction protocols that require milder conditions has become an important goal in this area of research. This review article comprehensively highlights the synthesis and mechanistic aspects of direct C–H arylation reactions, which proceed at or below room temperature.1 Introduction2 Concepts and Examples2.1 Transition-Metal-Catalyzed Procedures2.1.1 Pd Catalysis2.1.2 Other Metal-Based Procedures2.1.3 Additive-Free Procedures2.2 Direct Arylation Polymerization2.3 Photocatalyzed Procedures2.3.1 Organometallic C–H-Activation-Based Procedures2.3.2 Radical-Addition-Based Procedures2.4 Transition-Metal-Free Procedures2.4.1 Base-Mediated Procedures2.4.2 Iodonium- and Diazonium-Salt-Based Procedures2.5 Electrocatalyzed Procedures3 Summary and Outlook
Keywords: direct C–H arylation; mild reaction conditions; room temperature; transition-metal-catalyzed; photocatalyzed; electrocatalyzed